A Systematic Review of Identity and Access Management Requirements in Enterprises and Potential Contributions of Self-Sovereign Identity - Jana Glöckler; Johannes Sedlmeir; Muriel Frank; Gilbert Fridgen (Business & Information Systems Engineering, 2023)
Digital identity and access management (IAM) poses significant challenges for companies. Cyberattacks and resulting data breaches frequently have their root cause in enterprises' IAM systems. During the COVID-19 pandemic, issues with the remote authentication of employees working from home highlighted the need for better IAM solutions. Using a design science research approach, the paper reviews the requirements for IAM systems from an enterprise perspective and identifies the potential benefits of self-sovereign identity (SSI) – an emerging, passwordless paradigm in identity management that provides end users with cryptographic attestations stored in digital wallet apps. To do so, this paper first conducts a systematic literature review followed by an interview study and categorizes IAM system requirements according to security and compliance, operability, technology, and user aspects. In a second step, it presents an SSI-based prototype for IAM, whose suitability for addressing IAM challenges was assessed by twelve domain experts. The results suggest that the SSI-based authentication of employees can address requirements in each of the four IAM requirement categories. SSI can specifically improve manageability and usability aspects and help implement acknowledged best practices such as the principle of least privilege. Nonetheless, the findings also reveal that SSI is not a silver bullet for all of the challenges that today's complex IAM systems face.
Keywords: 000; Authentication; Digital wallet; IAM; Security; SSI; Verifiable credential